Study on the use of SSR markers linked to rust resistance for identification of F3 inbreed groundnut lines obtained by a cross between ICG950166 and L12 cultivars - Phòng, Đinh Thị; Thủy, Chu Thị; Thắng, Bùi Văn; Thắng, Nguyễn Văn; Yến, Nguyễn Thị; Bình, Lê Trần; Muội, Lê Thị (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 89-98, 2005